2019
DOI: 10.1002/mnfr.201801214
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Infant Fecal Microbiota Composition and Human Milk Oligosaccharide Consumption by Microbiota of 1‐Month‐Old Breastfed Infants

Abstract: Scope Understanding the biological functions of human milk oligosaccharides (HMOs) in shaping gastrointestinal (GI) tract microbiota during infancy is of great interest. A link between HMOs in maternal milk and infant fecal microbiota composition is examined and the role of microbiota in degrading HMOs within the GI tract of healthy, breastfed, 1‐month‐old infants is investigated. Methods and results Maternal breast milk and infant feces are from the KOALA Birth Cohort. HMOs are quantified in milk and infant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 61 publications
3
112
2
2
Order By: Relevance
“…infantis (B. infantis) and found that the organism is equipped with a gene set responsible for HMO assimilation [30]. Since then, various researchers have tried to elucidate the mechanisms of how bifidobacteria assimilate HMOs, and of how HMO consumption is related to the gut microbiota formation in breast-fed infant guts [12,[31][32][33][34][35][36][37]. Currently, breast-feeding is considered to be one of the most efficient strategies to shape healthy gut microbiotas during infancy [14,38].…”
Section: Introductionmentioning
confidence: 99%
“…infantis (B. infantis) and found that the organism is equipped with a gene set responsible for HMO assimilation [30]. Since then, various researchers have tried to elucidate the mechanisms of how bifidobacteria assimilate HMOs, and of how HMO consumption is related to the gut microbiota formation in breast-fed infant guts [12,[31][32][33][34][35][36][37]. Currently, breast-feeding is considered to be one of the most efficient strategies to shape healthy gut microbiotas during infancy [14,38].…”
Section: Introductionmentioning
confidence: 99%
“…longum (B. longum), are frequently detected in the stool of breast-fed infants. Many studies [9][10][11][12][13][14][15][16][17][18][19] have indicated that the formation of a bifidus-flora in the gut of breast-fed infants can be attributed to human milk oligosaccharides (HMOs), which are the third most abundant solid component in breastmilk after lactose and lipids [20][21][22]. Mothers produce the energy-rich HMOs, even though HMOs have no direct nutritional value for infants, as HMOs are resistant to digestive enzymes secreted in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…After birth, nutrition is one of the sources of polyamines, contributing to those produced by the organs of the digestive system and the microbiota. For primary amines (except for isoamylamine, present in breast milk), the main source is produced by intestinal bacteria, which may vary depending on the feeding type of newborns (56,57,72) . Through breast milk, the mother's microbiota is transferred and helps in establishing the newborns' own microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…While increases in the production of spermidine, spermine and histamine in several Gram-positive and Gramnegative strains have been demonstrated (73) . It is not easy to extrapolate this in vitro experiment, a cocktail with a fixed concentration of amines (0•03 %), with the variable conditions of the nutritional factors (72,74) and microbiota (56,57,75,76) found in newborns during lactation. But it suggests that the ingested polyamines and isoamylamine may contribute to facilitating or limiting the growth of different faecal bacteria strain producers or degraders of biogenic amines.…”
Section: Discussionmentioning
confidence: 99%